MEASURING LEADERSHIP EFFECTIVENESS: AN EMPIRICAL STUDY OF CONTINGENCY THEORY - Ria Sakinah; Aryanti, Vionaliza Okta R., Oktavian Windar P., M. Isa Anshori (Adisam Publisher, 2024)
This research aims to measure leadership effectiveness with an empirical study on contingency theory. The method used in this research is the SLR (Systematic Literature Review) method, which is a method used referring to certain research methodologies and development processes to capture or collect and publish research related to certain topics. Data collection was carried out secondaryly, namely by digging up information through previous research, reading from books, journals or websites that support this research. The results of this research state that in the practice of contingency theory of leadership in organizations, a leader must adapt to various situations, environmental conditions and company culture. Contingency theory is able to support organizations to achieve optimal goals.